2002
DOI: 10.1111/j.2042-7174.2002.tb00664.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of dispensing errors in NHS hospitals

Abstract: Focal points

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 1 publication
(2 reference statements)
5
50
0
Order By: Relevance
“…The most commonly reported dispensing error was dispensing wrong drug. Previous studies have reported dispensing wrong drugs in all types of inpatient settings [25,[32][33][34][35]. Omission due to drug unavailability was also a common error identified.…”
Section: Discussionmentioning
confidence: 94%
“…The most commonly reported dispensing error was dispensing wrong drug. Previous studies have reported dispensing wrong drugs in all types of inpatient settings [25,[32][33][34][35]. Omission due to drug unavailability was also a common error identified.…”
Section: Discussionmentioning
confidence: 94%
“…[3,33,37,39,41,43,44,47,72] In contrast, labelling medicines with the wrong directions, dispensing the wrong drug and strength were the most common prevented dispensing incidents in hospitals with manual and automated dispensing systems (Figure 6). [3,[33][34][35]43,46,72] Five papers investigated the impact of automation on the types of dispensing errors.…”
Section: Incidence In Brazilmentioning
confidence: 99%
“…O t h e r Figure 5 Most common types of unprevented dispensing incidents reported by UK hospital pharmacies with manual [3,33,37,39,41,43,44,47,72] and automated [44,47,72] dispensing systems. Where ( ) Spencer [3] (n = 178); ( ) James [72] (n = 35); ( ) Roberts [37] (n = 7158); ( ) James [44] postautomation (n = 14); ( ) Roberts [41] (n = 2068); ( ) Beso [43] (n = 32); ( ) James [44] pre-automation (n = 42); ( ) Bower [33] (n = 21); ( ) James [47] (n = 1005); ( ) Barker [39] (n = 208).…”
Section: Error Types In the Usmentioning
confidence: 99%
See 2 more Smart Citations